The Cambridge history of ancient Christianity (Cambridge, UK ; New York, NY)
xv, 698 sayfa
Keywords: “This volume engages constructive scholarly developments that have gained momentum within the study of pre-Constantinian Christianity in recent years. Each chapter represents cutting edge research. The most pressing questions of recent decades have been reviewed, and each contributor offers constructive ways forward for future research.“ --